Nell‐1‐ΔE, a novel transcript of Nell‐1, inhibits cell migration by interacting with enolase‐1. Issue 7 (16th April 2018) - Zhao, Huaxiang; Qin, Xueyan; Zhang, Qian; Zhang, Xinli; Lin, Jiuxiang; Ting, Kang; Chen, Feng
Abstract: NELL‐1 is a secreted protein that was originally found to be upregulated in pathologically fusing and fused sutures in non‐syndromic unilateral coronal synostosis patients. Apart from the ability of NELL‐1 to promote osteogenesis in long and craniofacial bones, NELL‐1 reportedly inhibits the formation of several benign and malignant tumors. We previously identified a novel transcript of Nell‐1 that lacked a calcium‐binding epidermal growth factor (EGF)‐like domain compared with full‐length Nell‐1 ; this new transcript was named Nell‐1‐ΔE . Three obvious structural differences between these two isoforms were revealed by homology modeling. Furthermore, the recombinant Nell‐1‐ΔE protein, but not the full‐length Nell‐1 protein, inhibited cell migration in vitro. However, full‐length Nell‐1 and Nell‐1‐ΔE proteins were present in similar subcellular locations and displayed similar expression patterns in both the intracellular and extracellular spaces. The results from the co‐immunoprecipitation and liquid chromatography/tandem mass spectrometry analyses using two cell lines demonstrated that Nell‐1‐ΔE but not full‐length Nell‐1 interacted with enolase‐1 in the extracellular spaces of both cell lines. The results of wound healing assays using ENO‐1‐overexpressing cells treated with full‐length Nell‐1/Nell‐1‐ΔE suggested that Nell‐1‐ΔE inhibited cell migration by interacting with ENO‐1. Our study indicated that the novel transcript Nell‐1‐ΔE, but not full‐length Nell‐1, might be a candidate tumor suppressor factor for basic research and clinical practice. Abstract : We identified a novel transcript of Nell‐1, named Nell‐1‐ΔE, which lacked sequences encoding an EGF‐like domain compared with full‐length Nell‐1. Nell‐1‐ΔE exhibited properties that were similar but not identical to those of full‐length Nell‐1, especially regarding inhibition of cell migration. Using co‐IP and LC‐MS/MS, we demonstrated that Nell‐1‐ΔE but not full‐length Nell‐1 interacts with ENO‐1 in the extracellular space.